2021
DOI: 10.1186/s12284-021-00516-6
|View full text |Cite
|
Sign up to set email alerts
|

Global Survey of Alternative Splicing in Rice by Direct RNA Sequencing During Reproductive Development: Landscape and Genetic Regulation

Abstract: Alternative splicing is a widespread phenomenon, which generates multiple isoforms of the gene product. Reproductive development is the key process for crop production. Although numerous forms of alternative splicing have been identified in model plants, large-scale study of alternative splicing dynamics during reproductive development in rice has not been conducted. Here, we investigated alternative splicing of reproductive development of young panicles (YP), unfertilized florets (UF) and fertilized florets (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…The analysis of AS events contributes to a better understanding of gene functions in the developmental process of animal species. 28 , 62 , 63 In the current study, the most abundant splicing events within the hub genes were the SE type, accounting for 23.63% of total AS events. Chacko and Ranganathan 64 also found that the majority of SE events were present in the bovine genome.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The analysis of AS events contributes to a better understanding of gene functions in the developmental process of animal species. 28 , 62 , 63 In the current study, the most abundant splicing events within the hub genes were the SE type, accounting for 23.63% of total AS events. Chacko and Ranganathan 64 also found that the majority of SE events were present in the bovine genome.…”
Section: Discussionmentioning
confidence: 53%
“… 26 DRS plays a vital role in dissecting the genotype-phenotype relationships that could reflect all aspects of testicular growth and development. To date, DRS technology has been adopted in identifying full-length splice isoforms, 27 exploring post-transcriptional events, 28 characterizing poly(A) tail lengths of transcripts, 29 improving the existing genome assembly, 30 and detecting RNA modifications. 31 Nevertheless, the DRS technology adopted for clarifying the transcriptome complexity has still not been widely applied in farm animal species, which delays the characterization and application of true transcriptomics in livestock industry.…”
Section: Introductionmentioning
confidence: 99%
“…We observed all four AS patterns: IR, ES, Alt 5′ss, and Alt 3′ss (Reddy et al ., 2013). This finding is consistent with the results of previous AS studies conducted in rice (Wei et al ., 2017; H. Li et al ., 2021). Intron retention events were more prevalent, closely followed by Alt 5′ss and Alt 3′ss, with a small percentage of transcripts affected by ES.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some clues can be obtained from recent studies. A great number of genes encoding splicing factors, miRNAs, long noncoding RNAs (lncRNAs), and transcription factors were found to undergo AS in young panicles and florets of rice (Li et al, 2021). The same genes from different rice genotypes carried out differential AS regulations in response to salt stress stimulation (Jian et al, 2022).…”
Section: Discussionmentioning
confidence: 99%